1981
DOI: 10.1002/1097-0142(19810315)47:6<1369::aid-cncr2820470622>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of prechemotherapy skin tests in patients with metastatic breast carcinoma

Abstract: Two hundred patients with metastatic breast cancer who were treated with combination chemotherapy and nonspecific immunotherapy with BCG or MER were skin tested prior to, and at regular intervals during the administration of chemotherapy with a battery of six antigens (Dermatophytin, Varidase, candida, mumps, PPD, and KLH). Delayed-type hypersensitivity responses to this battery of antigens were analyzed to assess whether they correlated with ability to respond to chemotherapy, length of survival, and a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Therefore, this parameter cannot be used for prognosis, which is in agreement with results reported by Hortobagyi et al [31]. Therefore, this parameter cannot be used for prognosis, which is in agreement with results reported by Hortobagyi et al [31].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, this parameter cannot be used for prognosis, which is in agreement with results reported by Hortobagyi et al [31]. Therefore, this parameter cannot be used for prognosis, which is in agreement with results reported by Hortobagyi et al [31].…”
Section: Discussionsupporting
confidence: 90%
“…The CMI Multitest was also administered, and the development of DTH skin test responses was measured at 48 hours in the same manner as for the DTH responses against KLH. A positive cutaneous DTH response against KLH was defined as an induration of greater than 2 mm (17). The criterion for nonresponse (anergy) on the CMI Multitest was no response of at least 2 mm (7).…”
Section: Immune Measuresmentioning
confidence: 99%
“…DTH skin test responses against KLH can be reliably elicited in human subjects (6,15), and an appropriate immunization protocol has been developed (6). In addition, cutaneous DTH against KLH may be indicative of overall cellular immune competence since responsiveness to KLH has been shown to correlate with responsiveness to a battery of prognostic antigens (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with recurrent breast cancers, Cunningham et a1 [7] found that patients with a strong DCH reaction to DNCB had a significantly higher probability of surviving at 52 and 78 weeks, a longer median length of survival, and a greater probability of responding to therapy. In patients with metastatic breast cancer, Hortobagyi et a1 [18] found that DCH to any of six recall antigens or the number of positive skin test responses did not correlate with overall or complete response rate to chemotherapy. This correlation did exist with KLH.…”
Section: Discussionmentioning
confidence: 98%